2016
DOI: 10.1038/srep24251
|View full text |Cite
|
Sign up to set email alerts
|

MHC-class-II are expressed in a subpopulation of human neural stem cells in vitro in an IFNγ–independent fashion and during development

Abstract: Expression of major histocompatibility antigens class-2 (MHC-II) under non-inflammatory conditions is not usually associated with the nervous system. Comparative analysis of immunogenicity of human embryonic/fetal brain-derived neural stem cells (hNSCs) and human mesenchymal stem cells with neurogenic potential from umbilical cord (UC-MSCs) and paediatric adipose tissue (ADSCs), while highlighting differences in their immunogenicity, led us to discover subsets of neural cells co-expressing the neural marker SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 45 publications
2
34
0
9
Order By: Relevance
“…Using human neural stem cells, Patrizia Ferretti (University College London, UK) reported recent progress on the development of 3D culture systems to study neural damage. She also showed that in developing human brains major histocompatibility complex class II antigens (MHC-II) are unexpectedly expressed in the germinal zone in a subset of SOX2-positive neural progenitors (Vagaska et al, 2016). This expression, which is seemingly regulated independently of inflammatory stimuli, challenges the accepted notion that microglia are the only MHC-II-expressing cells in the developing CNS.…”
Section: Regeneration Of the Cnsmentioning
confidence: 68%
“…Using human neural stem cells, Patrizia Ferretti (University College London, UK) reported recent progress on the development of 3D culture systems to study neural damage. She also showed that in developing human brains major histocompatibility complex class II antigens (MHC-II) are unexpectedly expressed in the germinal zone in a subset of SOX2-positive neural progenitors (Vagaska et al, 2016). This expression, which is seemingly regulated independently of inflammatory stimuli, challenges the accepted notion that microglia are the only MHC-II-expressing cells in the developing CNS.…”
Section: Regeneration Of the Cnsmentioning
confidence: 68%
“…Neuronal differentiation. A protocol previously modified from Sun et al 14,16 was used to induce neuronal differentiation of hNSCs 14,16 . After plating on Matrigel or laminin coated plates, hNSCs were maintained for 10 days in growth medium without EGF and then for further 7 days without EGF, FGF-2 and heparin to induce differentiation.…”
Section: Human Neural Stem Cells (Hnscs) Isolation Of Hnscs All Promentioning
confidence: 99%
“…Whereas the use of iPSCs (induced pluripotent stem cells) derived from patients to study neural diseases has been rapidly expanding, there is still a lack of human injury models particularly in 3D 11-13 .Here we have used human neural stem cells (hNSCs) derived from embryonic and foetal brain as a cell source for setting up 3D cultures and injury models 10,14,15 . The advantage of hNSCs over iPSCs or hESCs (human embryonic stem cells) for this purpose is that they can proliferate extensively in vitro, have the potential to differentiate towards neurons, astrocytes and oligodendrocytes and are less demanding than iPSCs to maintain in culture [14][15][16][17][18] . Furthermore, in comparison with iPSCs, hNSCs differentiation protocols are in general much shorter, as they do not require the initial phase of inducing the cells towards neural progenitors.We set out to establish and evaluate a 3D human cell culture system using hydrogel scaffolds in order to mimic in vivo CNS tissue architecture while maintaining reproducibility and minimising variation found in open Scientific RepoRtS | (2020) 10:6785 | https://doi.org/10.1038/s41598-020-62906-y www.nature.com/scientificreports www.nature.com/scientificreports/ Figure 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal VM tissue expresses MHC antigens that can elicit an immune response in the case of host mismatch (Widner et al, 1989). Expression level of MHC molecules is low in human PSCs and NSCs (Drukker et al, 2002;Vagaska et al, 2016) but can rapidly be induced in inflammatory conditions or following differentiation in vitro (Drukker and Benvenisty, 2004;Vagaska et al, 2016).…”
Section: Impact Of the Immune Status Of The Host Brainmentioning
confidence: 99%